2021
DOI: 10.1136/sextrans-2021-054985
|View full text |Cite
|
Sign up to set email alerts
|

How did COVID-19 measures impact sexual behaviour and access to HIV/STI services in Panama? Results from a national cross-sectional online survey

Abstract: ObjectiveTo describe reported changes in sexual behaviours, including virtual sex (sexting and cybersex), and access to HIV/STI testing and care during COVID-19 measures in Panama.MethodsWe conducted an online cross-sectional survey from 8 August to 12 September 2020 among adults (≥18 years) residing in Panama. Participants were recruited through social media. Questions included demographics, access to HIV/STI testing and HIV care, and sexual behaviours 3 months before COVID-19 social distancing measures and d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…At the same time, data from one of the convenience samples included in this analysis suggested that the convenience sample included similar proportions of adults within subnational geographic areas compared to census data. 30 Fourth, our study had fewer studies from low-income countries which may have been due to later COVID-19 initial waves and less capacity for research alongside the pandemic. At the same time, our main findings were robust when stratifying based on country income level.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…At the same time, data from one of the convenience samples included in this analysis suggested that the convenience sample included similar proportions of adults within subnational geographic areas compared to census data. 30 Fourth, our study had fewer studies from low-income countries which may have been due to later COVID-19 initial waves and less capacity for research alongside the pandemic. At the same time, our main findings were robust when stratifying based on country income level.…”
Section: Discussionmentioning
confidence: 96%
“…Third, our sample included more women, people with higher education, and people living in high-income countries compared with populations in respective countries. At the same time, data from 1 of the convenience samples included in this analysis suggested that the convenience sample included similar proportions of adults within subnational geographic areas compared with census data [ 34 ]. Fourth, our study had fewer studies from low-income countries, which may have been due to later COVID-19 initial waves and less capacity for research alongside the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A major structural barrier related to ART access was influenced by cost and distance to travel to the clinic. This barrier was, without a doubt, exasperated by the COVID-19 pandemic in 2020 and 2021, where the Covidization of healthcare significantly influenced HIV care [ 35 ]. Prior to the pandemic, we found that patients were expected to retrieve ART monthly and participate in biannual CD4 count and/or HIV plasma viral load check-ups during our data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Service interruptions caused by COVID-19 are hurting efforts around the world to end the HIV, TB, and malaria epidemics. According to simulations done by the HIV Modelling Consortium, in collaboration with the World Health Organisation (WHO) and UNAIDS, a 50 percent disruption in HIV treatment for six months could cause 300,000 more AIDS related deaths in sub-Saharan Africa over the course of a year [14,39]. In 2019, 440, 000 people in this region died from AIDS related illnesses, so this brings us back to AIDS related mortality levels in 2011.…”
Section: Impact Of Covid-19 On Access To Hiv Servicesmentioning
confidence: 99%